Developing a numeracy diagnostic assessment module for early primary students in the post COVID-19 pandemic - Mardyanto Barumbun (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2023)
School closures due to the COVID-19 pandemic have resulted in learning loss in primary school students, so a diagnosis of the students' numeracy skills is urgently needed at the beginning of learning to adapt learning to students' average ability levels (teaching at the right levels). This study aimed to develop a module that can assist and become a reference for teachers in schools in diagnosing and mapping students' numeracy abilities at the beginning of learning. Therefore, this research was carried out following the procedures of research and development (R&D). Prior to implementation, the developed module was validated by two experts (media and material experts) with validation results in â€œvery goodâ€ categories for each aspect of the material, layout, and graphics. The results of the study based on the teacher's response questionnaire indicate that the module developed is very helpful for the teachers in mapping students' numeracy abilities at the beginning of learning after the COVID-19 pandemic and provides an alternative follow-up to the results of students' numeracy assessments. Thus, the developed module is suitable for use as a reference in conducting assessments regarding early primary school studentsâ€™ numeracy.Keywords:Â diagnostic assessment module, early primary students, numeracy, post COVID-19 pandemic